Respuesta :
Step: Solve
2
x
+
y
=
3
for y:
2
x
+
y
=
3
2
x
+
y
+
−
2
x
=
3
+
−
2
x
(Add -2x to both sides)
y
=
−
2
x
+
3
Step: Substitute
−
2
x
+
3
for
y
in
4
x
+
3
y
=
1
:
4
x
+
3
y
=
1
4
x
+
3
(
−
2
x
+
3
)
=
1
−
2
x
+
9
=
1
(Simplify both sides of the equation)
−
2
x
+
9
+
−
9
=
1
+
−
9
(Add -9 to both sides)
−
2
x
=
−
8
−
2
x
−
2
=
−
8
−
2
(Divide both sides by -2)
x
=
4
Step: Substitute
4
for
x
in
y
=
−
2
x
+
3
:
y
=
−
2
x
+
3
y
=
(
−
2
)
(
4
)
+
3
y
=
−
5
(Simplify both sides of the equation)
Answer:
x
=
4
and
y
=
−
5
2
x
+
y
=
3
for y:
2
x
+
y
=
3
2
x
+
y
+
−
2
x
=
3
+
−
2
x
(Add -2x to both sides)
y
=
−
2
x
+
3
Step: Substitute
−
2
x
+
3
for
y
in
4
x
+
3
y
=
1
:
4
x
+
3
y
=
1
4
x
+
3
(
−
2
x
+
3
)
=
1
−
2
x
+
9
=
1
(Simplify both sides of the equation)
−
2
x
+
9
+
−
9
=
1
+
−
9
(Add -9 to both sides)
−
2
x
=
−
8
−
2
x
−
2
=
−
8
−
2
(Divide both sides by -2)
x
=
4
Step: Substitute
4
for
x
in
y
=
−
2
x
+
3
:
y
=
−
2
x
+
3
y
=
(
−
2
)
(
4
)
+
3
y
=
−
5
(Simplify both sides of the equation)
Answer:
x
=
4
and
y
=
−
5
Answer:
the value of x and y is 4 and -5 respectively.
Step-by-step explanation:
from the equation we say let;
2x + y = 3 .............. equation 1
4x + 3y = 1.............. equation 2
from equation 1
2x + y = 3 .............. equation 1
y = 3 - 2x................ equation 3
Substitute for y in equation 2
4x + 3y = 1.............. equation 2
we have,
4x + 3(3- 2x) = 1
4x + 9 -6x = 1
we have to collect the like terms
9-1 = 6x -4x
8 = 2x
divide both sides by 2
8/2 = 2x/2
4 = x
therefore x = 4
put x = 4 in equation 3
y = 3 - 2x................ equation 3
y = 3 - 2(4)
y = 3 -8
y = -5
therefore the value of x and y is 4 and -5 respectively.
to check if your answer is correct, put the value of x and y in any of the equations.
2x + y = 3 .............. equation 1
2(4) + (-5) = 3
8 -5 = 3
3 = 3......................... proved